2005
DOI: 10.1007/s00383-005-1547-x
|View full text |Cite
|
Sign up to set email alerts
|

Testis sparing surgery for steroid unresponsive testicular tumors of the congenital adrenal hyperplasia

Abstract: The association between testicular tumors/nodules and congenital adrenal hyperplasia (CAH) has been recognized for many years. Tumors are considered to be an aberrant adrenal tissue that has descended with the testes and has become hyperplastic due to ACTH stimulation. The recommended treatment consists of increasing the glucocorticoid dose to suppress ACTH secretions. If the testicular size is not reduced after suppression therapy or a side effect of glucocorticoid dose is noted, surgical intervention should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 10 publications
(13 reference statements)
0
29
0
11
Order By: Relevance
“…As a last resort, testis-sparing surgery might be considered in order to improve fertility. The results of surgery on fertility have been highly variable [174][175][176] and, in one of these studies, the recommendation was that surgery is only indicated for relief of pain and discomfort caused by the TARTs [176]. Surgery should probably only be considered for long-standing TARTs when testicular biopsies have demonstrated viable testicular tissue since surgery to improve fertility is uncertain.…”
Section: Testicular Adrenal Rest Tumors Tartsmentioning
confidence: 96%
“…As a last resort, testis-sparing surgery might be considered in order to improve fertility. The results of surgery on fertility have been highly variable [174][175][176] and, in one of these studies, the recommendation was that surgery is only indicated for relief of pain and discomfort caused by the TARTs [176]. Surgery should probably only be considered for long-standing TARTs when testicular biopsies have demonstrated viable testicular tissue since surgery to improve fertility is uncertain.…”
Section: Testicular Adrenal Rest Tumors Tartsmentioning
confidence: 96%
“…If the tumor size does not decrease, surgical intervention may be considered. Two studies have described testis-sparing enucleation of the tumor (21,22). However, whether improvement of gonadal function occurs after surgery remains unclear, so surgery should be reserved for the patients who do not respond to conservative treatment.…”
Section: Tablementioning
confidence: 96%
“…In cases of 21OHD with minimal response to increased dose of glucocorticoids or with persistent azoospermia, testis sparing surgery has been shown to improve fertility [150,151]. However, this is not a consistent finding and hence surgery should be performed only if testicular biopsy confirms viable testicular tissue [2,136].…”
Section: Testicular Adrenal Rest Tumorsmentioning
confidence: 98%